MODERN FEMALE DETECTIVE, CHARACTERISTICS AND INTERPRETATION - Smushchynska, Iryna; Tsyrkunova, Iryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
This article explores the development and current trends in the female detective genre, focusing on its transformation within Ukrainian and Spanish literature as a branch of mass literature. Over time, the genre has evolved from traditional mystery narratives to complex stories where women occupy central roles as detectives, often displaying nuanced psychological depth. The Ukrainian female detective novel typically emphasizes social issues, human relationships, and moral dilemmas, presenting protagonists as amateurs who rely on intuition. Conversely, the Spanish approach incorporates broader, often international themes, portraying women as professional investigators who utilize forensic methods and psychological profiling to solve cases. One notable example, La cara norte del corazón by Dolores Redondo, illustrates the Spanish genre’s orientation toward a global perspective, where the narrative integrates mystical elements to enhance suspense. This work highlights the Spanish approach of framing crime fiction in broader societal and psychological contexts. Differences between the Ukrainian and Spanish styles underscore the genre’s adaptability and its ability to reflect cultural and gender perspectives through accessible language and engaging plots. ___________ References: • Bessarab, O. «Detektyvnyy roman yak holovnyy proyav masovoyi literatury kinta XX - pochatku XXI stolittia.» Vісnyk Kharkivsʹkoho natsionalʹnoho universytetu im. V. N. Karazina, 2012, no. 1014, vyp. 65: 204-207. • Hulyak, T. «Zhankrova svoyedrivnistʹ ukrayinsʹkoho zhinochoho detektyvu.» Naukovyy visnyk Mizhnarodnogo humanitarnogo universytetu. Seriya: Filolohiya, 2018, no. 37: 153–156. • Dyachuk, L. S. Suchasna frantsuzʹka zhinocha proza v ukrayinsʹkykh perekladakh: avtoreferat ... kand. filol. nauk (Kyiv: KNU imeni Tarasa Shevchenka, 2016), 20 s. • Yermolenko, I. I. Kompozytsiine i komunikatyvno-prahmatychne konstruiuvannia “chornogo detektyvu” Daniyela Pennaka: avtoreferat ... kand. filol. nauk (Kyiv: KNLU, 2016), 20 s. • Zarubizhni pysʹmennyky. Entsyklopedychnyy dovidnyk u dvokh tomakh. Tom 1 (za red. N. Mykhalsʹkoyi ta B. Shchavursʹkoho) (Ternopilʹ: Bohdan, 2005), 823 s. • Kontsepty i kontseptosystemy: dynamichni vymiry (pid red. I. O. Holubovsʹkoyi, L. V. Klymenko) (Kyiv: Lohos, 2017), 178 s. • Ponomaryova, O. O. «Frantsuzʹkyy detektyvnyy humorystychniy tekst: teoretychni zasady doslidzhennia.» Problemy semantyky, slova, rechenni ta tekstu: zb. nauk. pr. (Kyiv, 2006), vyp. 17: 297–301. • Ponomaryova, O. O. Strukturno-kompozytsiyni ta komunikatyvno-prahmatychni osoblyvosti frantsuzʹkoho detektyvnoho humorystychnoho romanu: dysertatsiya ... kand. filol. nauk (Kyiv: KNLU, 2008), 204 s. • Soboleva, Y. Yu. Kontsept TAYEMNYTSIA ta yoho verbalizatsiya v ukrayinsʹkiy linhvokulturi: avtoreferat ... kand. filol. nauk (Kyiv: KNU imeni Tarasa Shevchenka, 2014), 18 s. • Taranova, A. O. «Detektyv ochyma zhinky.» Aktualʹni problemy slovyansʹkoyi filolohiyi: Mizhnuz. zb. nauk. statey, vyp. XIV: Lingvistyka i literaturoznavstvo (Nizhyn, TOV «Vydavnytstvo «Aspekt-Polihraf», 2007): 231-239. • Todorov, Tz. Ponyattya literatury ta inshi ese. Kyiv: Vyd. dim «Kyievo-Mohylanska akademiya», 2006, 162 s. • Romero Tabares, Isabel. «Literatura de masas: subgénero o nueva literatura?» Revista Crítica, 7 листопада 2015. https://www.revista-critica.es/2015/11/07/literatura-de-masas-subgenero-o-nueva-literatura/. • «Quels sont les 10 meilleurs policiers et thrillers en 2024?» Audible, 2024. https://www.audible.fr/blog/meilleurs-polars-thrillers-2024.